(untitled) (The Research of Medical Science Review, 2025)
BACKGROUND: Fistula in ano is a commonly encountered perianal condition resulting from infection of the anal glands within the intersphincteric space. It is often associated with significant patient discomfort and morbidity. While fistula in ano may occur in both sexes, epidemiological data suggest a higher prevalence among females globally. The management of high anal fistula remains a surgical challenge, and the cutting seton technique is among the methods employed for effective treatment. Objective: To evaluate the outcomes following cutting seton procedure for high anal fistula. METHODS: This descriptive study was conducted at the Department of General Surgery, Medical Teaching Institution (MTI), Khyber Teaching Hospital, Peshawar. A total of 171 patients diagnosed with high anal fistula underwent the cutting seton procedure. Demographic data, clinical characteristics, and surgical outcomes were recorded. Pain was assessed using the Visual Analogue Scale (VAS), while recurrence and incontinence were documented during follow-up. Outcomes were stratified by age, gender, BMI, socioeconomic status, profession, and fistula location. Chi-square test was applied, and a p-value ≤0.05 was considered statistically significant. RESULTS: The mean age of patients was 42.3 ± 11.4 years, with 60.8% being female. Postoperative pain was reported in 55.0% of patients (mean VAS score 4.8 ± 1.6). Recurrence occurred in 12.9%, and incontinence was observed in 18.1%, primarily to flatus. Stratification showed no significant associations between outcomes and demographic or clinical variables (p > 0.05 for all). CONCLUSION: The cutting seton procedure for high anal fistula is associated with acceptable rates of pain, recurrence, and incontinence. Outcomes were not significantly influenced by age, gender, BMI, or socioeconomic status, suggesting the technique may be effectively applied across diverse patient groups.